Сравнение динамических характеристик наблюдателей вектора состояния и неопределённости - Казурова, Алина Евгеньевна (Национальный технический университет "Харьковский политехнический институт", 2019)
На простом примере рассматривается позиционное управление нелинейной нестационарной неопределённой системой посредством робастного комбинированного компенсатора, состоящего из наблюдателя вектора состояния и неопределённости системы управления и регулятора. Проведено сравнение четырёх типов наблюдателей вектора состояния и неопределённости. В качестве измерения в системе выступает только позиционная координата. Компьютерное моделирование подтвердило работоспособность рассматриваемой системы управления.

On a simple example the position control of a nonlinear nonstationaryuncertain system is considered. The uncertainty of the systemis the inaccarately known moment of inertia, control and external actions. The robust combined compensator consisting of the state vector and control system uncertainty observer and a regulator is used to control this system. A comparison of the dynamic characteristics of the four type state vector and uncertainty observers: zero order (computer), first order, second order, and also a reduced observer, has been carried out. The first two types estimate only system uncertainty, and for getting information about state vector an asymptotic differentiator of positional coordinates is applied. Only the positional coordinate is used as a measurement in the system. The coefficients of the observers and the regulator were calculated using the standard Butterworth polynomials. The comparable observers use recommendations have beengiven. Computer simulation has confirmed functionality of the considered control system.
A comparison of the dynamic characteristics of the state vector and uncertainty observers
Keywords: позиционное управление; робастный комбинированный компенсатор; positional control; robust combined compensator